Anodic electron sheaths in low pressure hollow cathode discharge with large size anode - Bazhenov, V.Yu.; Matsevich, S.V.; Piun, V.M.; Tsiolko, V.V. (Вопросы атомной науки и техники, 2015)
Researches of the features of “electron” sheath formed between the negative glow plasma and the anode of hollow cathode discharge in oxygen and nitrogen at low pressure are performed. Peculiarities of behavior of spatial distributions of current onto the anode, plasma density and electron temperature are determined at different gas pressure and discharge current.